Effects of a Long COVID Literacy Enhancement Program on Reducing the Severity of Post-Infection COVID-19 Behaviors of Elderly in Communities, Bangkok Metropolitan Area - hlanden, kaewta; Jewpattanakul, Yupa; Koshakri, Rukchanok (Nursing Journal CMU, 2024)
Long COVID symptoms in elderly with COVID-19 affect their lives. Enhancing health literacy can reduce the severity of Long COVID symptoms. This randomized controlled trial explored the effects of a Long COVID literacy enhancement program on reduction of the severity of post-infection COVID-19 behaviors of elderly in Bangkok communities. The two-group pretest-posttest design applied Nutbeam’s health literacy as a conceptual framework. Sixty four elderly Bangkok residents, aged 60-80 years with COVID-19 for five days to two months were randomly assigned, by multi-stage random sampling with a computer, to an experimental group or a control group with 32 per group. The experimental group received the Long COVID literacy enhancement programe consisting of healthy dietary instruction; demonstrations on selecting online sources of knowledge about Long COVID via Google, Facebook, and YouTube; lung exercises; and breathing exercises for relaxing from stress. The participants were instructed to engage in lung and breathing exercises at home once a day and document their exercise for 12 weeks. Pretest and posttest data were analyzed with independent t-test and paired t-test statistics. The findings showed that the experimental group had a significantly higher mean score for reducing severity of post-infection COVID-19 behaviors after the experiment (M = 74.44, SD = 5.93) than before the experiment (M = 52.00, SD = 9.64, t = 9.78, p < .001). Moreover, the experimental group had a significantly higher mean score for reducing severity of post-infection COVID-19 behaviors after the experiment (M = 74.44, SD = 5.93) than the control group (M = 50.38, SD = 7.96, t = 13.70, p < .001). These findings provide a guideline for community nurse practitioners, professional nurses, and health teams to reduce the severity of symptoms of post-infection COVID-19 patients.